2014
DOI: 10.1523/jneurosci.3714-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Glial Wingless/Wnt Regulates Glutamate Receptor Clustering and Synaptic Physiology at theDrosophilaNeuromuscular Junction

Abstract: Glial cells are emerging as important regulators of synapse formation, maturation, and plasticity through the release of secreted signaling molecules. Here we use chromatin immunoprecipitation along with Drosophila genomic tiling arrays to define potential targets of the glial transcription factor Reversed polarity (Repo). Unexpectedly, we identified wingless (wg), a secreted morphogen that regulates synaptic growth at the Drosophila larval neuromuscular junction (NMJ), as a potential Repo target gene. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 56 publications
5
83
1
Order By: Relevance
“…Transmitter release at the Drosophila neuromuscular junction can be affected by the target muscle or the neighboring peripheral glia (Huang and Stern, 2002;Kerr et al, 2014;McCabe et al, 2003;Schmidt et al, 2012). RNAi-mediated atl knockdown in muscle or glia did not affect transmitter release or frequency of synaptic failures (Fig.…”
Section: Bip-sfgfp-hdel Marks the Ermentioning
confidence: 95%
See 1 more Smart Citation
“…Transmitter release at the Drosophila neuromuscular junction can be affected by the target muscle or the neighboring peripheral glia (Huang and Stern, 2002;Kerr et al, 2014;McCabe et al, 2003;Schmidt et al, 2012). RNAi-mediated atl knockdown in muscle or glia did not affect transmitter release or frequency of synaptic failures (Fig.…”
Section: Bip-sfgfp-hdel Marks the Ermentioning
confidence: 95%
“…In particular, loss of activity within the peripheral glia of the kinesin heavy chain gene or the inebriated-encoded neurotransmitter transporter alters evoked transmitter release (Huang and Stern, 2002;Schmidt et al, 2012). In addition, the peripheral glia secrete at least two proteins, the TGF-β ligand Maverick and Wingless/Wnt, that regulate synaptic function (Fuentes-Medel et al, 2012;Kerr et al, 2014). The muscle, in turn, secretes the BMP ligand Gbb to regulate both evoked transmitter release and motor neuron arborization (McCabe et al, 2003).…”
Section: Rtnl1 Affects Evoked Neurotransmitter Release From Multiple mentioning
confidence: 99%
“…These synapses are glutamatergic, stereotypically positioned, and resemble mammalian central synapses in terms of the neurotransmitter used [50,51] . Compelling evidence has shown that glia, closely associated with these synapses, modulate synaptic activity and synapse formation [52][53][54][55][56] .…”
Section: Glia-derived Factors During Synapse Formation and Functionmentioning
confidence: 99%
“…Wingless factor Reversed polarity (Repo), is secreted by glia to mediate postsynaptic glutamate receptor clustering [55] .…”
Section: Glia-derived Factors During Synapse Formation and Functionmentioning
confidence: 99%
See 1 more Smart Citation